IDEAL BUILDING TO PREVENT THE RISK OF COVID-19 TRANSMISSION - Yuliana (Border: Jurnal Arsitektur, 2021)
COVID-19 pandemic has been more than one year. Closed and less ventilation building has higher risk for COVID-19 transmission. The risk will be higher if the building has air conditioner. The problem is how if the building is a permanent building and it is difficult to be changed. This paper aims to describe the ideal building to reduce the COVID-19 transmission. Method is literature review. Databases were Science Direct and Google Scholar. Keywords were building, COVID-19, ideal, transmission. Results shows that filtration, adequate ventilation, air disinfection, and avoiding recirculation are important ways to prevent the transmission. This can be done also by preventing overcrowding. This is suitable to be implemented in public places that are usually visited by many people. Conclusion: ideal building for preventing COVID-19 transmission is having proper ventilation and avoiding recirculation. This condition is important for public places such as hospitals and schools to prevent the COVID-19 transmission risks.